A COMPARATIVE STUDY ON POWER CALCULATION METHODS FOR CONVEYOR BELTS IN MINING INDUSTRY. Issue 1 (2nd January 2022) - Köken, Ekin; Lawal, Abiodun Ismail; Onifade, Moshood; Özarslan, Ahmet
ABSTRACT: This paper covers different methods to evaluate the power consumption of several conveyor belt systems (CBSs) used in the Turkish Mining Industry (TMI). Based on each CBS's operational features, the power consumption (Pc, kW) was measured directly on motorised head-pulleys. The Pc was investigated through several conventional, statistical, and machine learning methods. This study shows that the DIN 22, 101 could be the most convenient conventional method for the investigated CBSs. On the other hand, based on the nonlinear regression (NLR) and genetic expression programming (GEP) models, two new approaches were suggested for the design and optimisation of the Pc .